Endoscopic Orientation of Juxta-pituitary Carotid in Transsphenoidal Approaches: Critical Considerations for Clinical Applications - Mostafa Ismail; Mohab Darwish; Abd El Rahman El Tahan; Islam R. Herzallah (International Archives of Otorhinolaryngology, 2023)
Introduction In sphenoid sinuses with ill-defined carotid bony landmarks, accidental injury of the internal carotid artery (ICA) remains one of the most challenging complications, which is particularly reported in the endoscopic endonasal transsphenoidal approaches (EETAs).